Self-Compacting Concrete with Artificial Lightweight Aggregates from Sugarcane Ash and Calcined Scheelite Mining Waste - Jemima Tabita F. de Sousa; Marcos Alyssandro S. dos Anjos; José Anselmo da S. Neto; Evilane C. de Farias; Fernando G. Branco; Cinthia Maia Pederneiras (Applied Sciences)
Self-compacting concrete (SCC) is a relevant technology and an alternative to conventional concrete in complex structures due to its exceptional workability. The rheological parameters demonstrated by SCC provide high fluidity and cohesion, resulting in high mould-filling capability and segregation resistance, as well as optimising concreting processes and reducing costs. In view of this, self-compacting lightweight concrete (SCLC) has emerged as a possible alternative as it combines the benefits of SCC and lightweight aggregate concrete (LWAC). In the production of LWC, the most widely used lightweight aggregate in the world, and also in Brazil, is still expanded clay; however, Brazilian production is restricted to the southeast region. In this context, previous studies have verified the feasibility of producing lightweight aggregates from the sintering of industrial waste and regional raw materials (Rio Grande do Norte/Brazil), such as sugarcane bagasse ash (SBA), scheelite mining residue (SMR), and local clay. Therefore, this study evaluates the influence of three lightweight aggregates, analysing their performance in comparison with SCLC produced with commercial lightweight aggregate (expanded clay). The concretes studied were subjected to characterisation tests in a fresh state; fluidity, apparent viscosity, visual stability, and passing ability were assessed through slump flow tests, flow time (T500), visual stability index, and J-ring, respectively, as well as measurement of the fresh specific mass. In the hardened state, tests were carried out to determine the compressive strength at 7 and 28 days, the dry specific mass, the chloride ion diffusion coefficient, and the thermal conductivity. The new concretes had density values ranging from 1.94 to 2.03 g/cm3 and compressive strength values at 28 days between 26.11 and 36.72 MPa. The results obtained show that it is feasible to produce SCLC with unconventional lightweight aggregates based on sugarcane bagasse waste and scheelite mining waste.